THE CORRELATION BETWEEN PHYSICAL ACTIVITY AND STRESS AND THEIR IMPACT ON URIC ACID LEVELS IN OLDER INDIVIDUALS - Priyanto, Agus; Abdillah, Alvin; J, Luluk Fauziyah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
The elderly population, who are more susceptible to infection and chronic illnesses, are particularly susceptible to gout. The Pakong Health Center Working Area has a high prevalence of gout among the elderly population. The study examines the relationship between physical activity and stress, with uric acid levels as the dependent variable. The study involved 60 patients with gout, with a sample size of 53. The DASS physical activity questionnaire was used to gather data. The results showed that 77% of participants engaged in moderate physical activity, while almost 40% fell into the moderate stress group. The majority of uric acid levels were elevated, with 36 out of 68% being elevated. The Spearman Rank analysis yielded a p-value of 0.005, indicating a correlation between physical activity and uric acid levels in the elderly. Additionally, a p-value of 0.000, indicating a link between stress levels and gout occurrence, suggests that older individuals should enhance their physical activity and manage their nutrition to lower uric acid levels. Additionally, seniors should reduce stress by improving their religious practices, expressing their concerns, and maintaining a positive mindset.